Incidence of heart disease in 35,000 women treated with radiotherapy for breast cancer in Denmark and Sweden. - McGale, P; Darby, S; Hall, P; Adolfsson, J; Bengtsson, N; Bennet, A; Fornander, T; Gigante, B; Jensen, M; Peto, R; Rahimi, K; Taylor, C; et al. (2011)
PURPOSE: To study incidence of radiation-related heart disease in a large population of breast cancer patients followed for up to 30 years. MATERIAL AND METHODS: 72,134 women diagnosed with breast cancer in Denmark or Sweden during 1976-2006 and followed prospectively. Radiation-related risk was studied by comparing women with left-sided and right-sided tumours. RESULTS: 34,825 women (48%) received radiotherapy. Among unirradiated women tumour laterality had little relevance to heart disease. Among irradiated women mean dose to the whole heart was 6.3 Gy for left-sided tumours and 2.7 Gy for right-sided tumours. Mortality was similar in irradiated women with left-sided and right-sided tumours, but incidence ratios, left-sided versus right-sided, were raised: acute myocardial infarction 1.22 (95% CI 1.06-1.42), angina 1.25 (1.05-1.49), pericarditis 1.61 (1.06-2.43), valvular heart disease 1.54 (1.11-2.13). Incidence ratios for all heart disease were as high for women irradiated since 1990 (1.09 [1.00-1.19]) as for women irradiated during 1976-1989 (1.08 [0.99-1.17]), and were higher for women diagnosed with ischaemic heart disease prior to breast cancer than for other women (1.58 [1.19-2.10] versus 1.08 [1.01-1.15], p for difference=0.01). CONCLUSIONS: Breast cancer radiotherapy has, at least until recently, increased the risk of developing ischaemic heart disease, pericarditis and valvular disease. Women with ischaemic heart disease before breast cancer diagnosis may have incurred higher risks than others.